Ruptura de enlaces α (1,6) de la dextrana mediante la enzima dextranaza para la obtención de moléculas de glucosa y su aprovechamiento posterior en etanol en la empresa Casa Grande S.A.A. - Loyola Moreno, Lucy Giovanna (2013)
The purpose of this thesis is to solve the problem generated in the Sugar Company CASAGRANDE S.A.A referring to the dextran present in the sugar cane and throughout the industrial process of obtaining the sugar. This means achieving a higher return on sugar production and therefore increasing the economic profit of the company in question. This problem has been solved by the use of the enzyme Dextranase in order to break the α (1,6) bonds of Dextran, recovering glucose from the sucrose polymerized by Dextran and taking advantage of it to obtain ethanol. All this raised the challenge of putting into practice an efficient methodology based on the adequate and effective dosing of the enzyme Dextranase at 10, 15, 25, 30, 60 ppm and times of 10, 20 and 30 minutes in syrup type A, B and C. In this way, the levels of Dextran were lowered and the highest amount of glucose was recovered to obtain ethanol, with the optimum efficiency being the dosage of 15 ppm Dextranase enzyme and a time of 20 minutes in the application of syrups. Therefore, this thesis is aimed at reducing the levels of dextran originating from sugarcane harvesting, which is detrimental because it increases the viscosity in the juices and consumes the sucrose irreversibly. Achieving this decrease is achieved increase sugar production, in addition to obtaining ethanol from the glucose recovered in sucrose. And lastly, it is possible to promote the sustainable development of the company aimed at its economic growth by generating higher economic incomes